Public service motivation: a systematic literature review and outlook - Ritz, Adrian; Neumann, Oliver; Brewer, Gene A. (2016)
Over the past two decades, research on public service motivation has seen rapid growth. Despite the relatively large number of publications to date, no systematic research overview has been created, leaving the body of literature somewhat unstructured and possibly hampering future research. This article fills this void by providing a systematic literature review of 323 publications that examines six key aspects of the literature on public service motivation: the growth of research on the concept, the most prominent studies based on a referencing network analysis, the most frequent publication outlets, research designs and methods, lines of inquiry and patterns of empirical findings, and implications for practice drawn from the publications in the study sample. Strengths and weaknesses of the existing literature are identified, and future research directions are proposed. - Reproduced.
Keywords: Motivation